Misdiagnosis of Tracher-Collins Syndrome Initially Attributed to Drug Teratogenicity: A Moroccan Case Report - Lamzouri A; EL Rherbi A; Ratbi I; Laarabi FZ; Chahboune R; Elalaoui SC; Hamdaoui H; Bencheikh RS; Sefiani A (Balkan Journal of Medical Genetics, 2024)
Treacher Collins syndrome (TCS) is a rare congenital disorder of craniofacial development characterized by numerous developmental anomalies that are restricted to the head and neck. Most TCS cases are inherited in an autosomal dominant manner. The diagnosis of TCS relies on clinical and radiographic findings. The four genes involved in TCS are TCOF1, POLR1D, POLR1C, and POLR1B.